Optimum viscous damper for connecting adjacent SDOF structures for harmonic and stationary white-noise random excitations. - Bhaskararao, A. V. (Earthquake engineering & structural dynamics.)
The dynamic behaviour of two adjacent single-degree-of-freedom (SDOF) structures connected with a viscous damper is studied under base acceleration. The base acceleration is modelled as harmonic excitation as well as stationary white-noise random process. The governing equations of motion of the connected system are derived and solved for relative displacement and absolute acceleration responses of connected structures. The response of structures is found to be reduced by connecting with a viscous damper having appropriate damping. For undamped SDOF structures, the closed-form expressions for optimum damping of viscous damper for minimum steady state as well as minimum mean square relative displacement and absolute acceleration of either of the connected SDOF structures are derived. The optimum damper damping is found to be functions of mass and frequency ratio of two connected structures. Further, numerical results had indicated that the damping of the connected structures does not have noticeable effects on the optimum damper damping and the corresponding optimized response. This implies that the derived closed-form expressions for optimum damper damping of undamped structures can also be used in practical applications for damped structures.